Determinants of Public Perception on Biotechnological Innovations - Kumar, K. L. Prasanna; Sujatha, B; Reddy, G Pakki; Subba Reddy, S V (Journal of Agricultural Extension Management, 2019)
Biotechnology is one of the key technologies which would resolve presentburning problems like climate change, pollution, malnutrition, drought andsalinity and lead to sustainable development. Biotechnology has become acomplex technology with its wide scope for generating multiple innovationsacross various industries. Unfortunately there are some apprehensions aboutbiotechnological innovations like r-DNA technology, cloning technology etc.Due to lack of reliable information on biotechnological innovations and theirutility in various industries, people are unable to perceive the merits anddemerits of biotechnology. Hence it is necessary to address these issues forsustainable scientific governance. In India, the rate of generation anddissemination of inventions in biotechnology is lagging due to societalagitation on use of Bt. technology in food crops like brinjal, maize etc. andethical concerns over GM animals. This study focuses on determinants ofpublic perception and attitude towards biotechnological innovations.